Impact of Encapsulation Wall Materials and Drying Method on Physicochemical Properties and Digestibility of Encapsulated Chayote (Sechium edule (Jacq.) Swartz) and Kohlrabi (Brassica oleracea var gongylodes L.) Extracts - Ploypetchara, Thongkorn; Sorndech, Waraporn; Auranwiwat, Chiramet; Sumsakul, Wiriyaporn; Pinthong, Monsicha; Kansuwan, Antika; Butseekhot, Siriporn; Siricoon, Sinee (Food Science and Engineering, 2021)
Chayote (Sechium edule (Jacq.) Swartz) and kohlrabi (Brassica oleracea var gongylodes L.) are medicinal plants widely distributed in Thailand. Several traditional medicines usually contain these extracts due to their pharmaceutical activities. However, appropriate technologies that are used for protection, stabilization, and slow release of plant extracts are a lot desired in terms of food application. In this study, chayote and kohlrabi extracts were encapsulated by several kinds of wall materials (maltodextrin, and the combination of maltodextrin and gum arabic or alginate) and drying methods (freeze-drying and tray-drying techniques). Thus, the objective of this research was to determine morphological and physicochemical properties, wall materials releasing, and antioxidant activity of encapsulated chayote and kohlrabi extracts powder. The morphology of all encapsulated chayote and kohlrabi extracts powder showed an irregular spherical shape, monodispersity, and smooth surface. The encapsulated chayote and kohlrabi extracts powder with the tray-drying technique tend to have more darkness and redness in color than the freeze-drying technique. Wall material release was expressed in glucose liberation of encapsulated extracts powder after amylolytic enzyme digestion. Encapsulation using maltodextrin as wall material provided higher wall material release than the other samples. After digestion analysis, the digested residues were examined for antioxidant activity. The results showed that the combination of maltodextrin and alginate for both freeze-drying and tray-drying techniques provided higher antioxidant activity after 60 and 120 min of digestion. Thus, the combination of maltodextrin and alginate, and drying with the freeze-drying technique was the best treatment in this experiment. This data can lead to a better understanding of wall materials types and releasing characteristics, which are used to control bioactive compounds liberation in the gastrointestinal tract.